Extending the Lifetime of Copper-beryllium Alloys as Plastic Injection High-end Needle Valve Mold Nozzle Tips Through a Heat-treatment-based Microstructure Optimization Approach - Meng, Xiaomin; Zhao, Dong; Majid, Shaker (Journal of Wuhan University of Technology-Materials Science Edition, 2023)
The relationship between the microstructure and the practical performance of two different copper-beryllium alloys including their lifetime has been investigated. Herein, two valves made of two different alloys with very similar compositions and the same heat treatment methods were investigated by various standard techniques including metallography, X-ray diffraction, chemical composition, microhardness, and thermal conductivity measurements. Although both alloys experienced the same heat-treatment processes, they revealed different thermal and mechanical properties due to the minor difference in their chemical composition. The alloy providing a longer lifetime (40% more) as the tip had a higher thermal conductivity of 280.3 W (m·K)−1 (about two times that of the other alloy). Regarding the metallography images and the measured thermal conductivity values of the alloys, the extended lifetime of the nozzle with the optimum performance is ascribed to its biphasic microstructure and the minor grain boundaries and interfacial thermal resistance. And important difference in the chemical composition was investigated in this study.
CRIS-Team Scopus Importer:2023-06-30
Keywords: crystal structure; grain boundaries; metals and alloys; needle valve; thermal properties